In situ repair or reconstruction of the abdominal aorta-iliac artery by autologous fascia-peritoneum with posterior rectus sheath for the treatment of the infected abdominal aortic and iliac artery aneurysms: A case series and literature review - Li, Lubin; Liu, Guolong; Yu, Benxiang; Niu, Wenqiang; Pei, Zhigang; Zhang, Juwen; Che, Haijie; Song, Fubo; Yang, Mu (Frontiers in Cardiovascular Medicine, 2022)
Background Infected abdominal aortic and iliac artery aneurysms are considered acute and severe diseases with insidious onset, rapid development, and high mortality in vascular surgery. Currently, there is no better treatment, either anatomic or extra-anatomical repair. Case presentation From February 2018 to April 2022, 7 patients with infected abdominal aortic and iliac artery aneurysms did not have sufficient autologous venous material for repair. With the consent of the Ethics Committee of the hospital, it uses the autologous peritoneal fascial tissue with rectus sheath to repair or reconstruct the infected vessels in situ. There were 5 cases of infected abdominal aortic aneurysm, 1 case of an infected common iliac aneurysm, and 1 case of the infected internal iliac aneurysm. Aortoduodenal fistula was found in 3 cases, all of them were given duodenal fistula repair and gastrojejunostomy and cholecystostomy. Three cases of infected abdominal aortic aneurysms were repaired with the autologous peritoneal fascial tissue patch, and 2 cases of infected abdominal aortic aneurysms were reconstructed by the autologous peritoneal fascial tissue suture to bifurcate graft in situ, the autologous peritoneal fascial tissue suture reconstructed the rest 2 cases of infected iliac aneurysm to tubular graft in situ. It was essential that Careful debridement of all infected tissue and adequate postoperative irrigation and drainage. Antibiotics were administered perioperatively, and all patients were subsequently treated with long-term antibiotics based on bacterial culture and susceptibility results of infected tissues and blood. All 7 patients had underwent surgery successfully. But there were 2 cases died of anastomotic infection or massive hemorrhage after the operation, the other 5 cases survived. The follow-up time was 2–19 months. The enhanced CT of postoperation showed that the reconstructed arteries were smooth without obvious stenosis or expansion, and no abdominal wall hernia occurred. Conclusion In situ repair or reconstruction with autologous peritoneal fascial tissue with rectus sheath is a feasible treatment for the infected aneurysm patients without adequate autologous venous substitute, but it still needs long-term follow-up and a large sample to be further confirmed.